Lessons from an American stoic : how Emerson can change your life - Matousek, Mark (HarperOne, an imprint of HarperCollinsPublishers, 2023)
"A lifelong Emerson lover, teacher, and spiritual seeker reveals how American philosopher Ralph Waldo Emerson's twelve essential teachings hold the answer to living an authentic and fulfilling life, one that is in harmony with our souls"--